Measuring what matters in the Great Barrier Reef. Issue 5 (7th May 2018) - Marshall, Nadine; Barnes, Michele L; Birtles, Alistair; Brown, Katrina; Cinner, Joshua; Curnock, Matt; Eakin, Hallie; Goldberg, Jeremy; Gooch, Margaret; Kittinger, Jack; Marshall, Paul; Manuel‐Navarrete, David; et al.
Abstract : The natural environment plays an integral role in the culture of all people. Although the cultural services provided by ecosystems are often acknowledged, these abstract qualities are difficult to capture and are rarely incorporated into environmental strategic planning. We propose an approach for decision makers to weigh different cultural values across a range of stakeholder groups. We assessed the importance of the Great Barrier Reef (GBR) to the lifestyle, sense of place, pride, identity, and well‐being of 8300 people across multiple cultural groups, as well as each of these groups' belief in the aesthetic, scientific, and biodiversity‐based value of the GBR. The surveyed population included indigenous and non‐indigenous local residents, Australians (non‐local), international and domestic tourists, tourism operators, and commercial fishers. We discuss how some groups grant similar levels of importance to some values and how other groups differ in their attachment to certain values. All of the groups possessed the selected cultural values to some extent, suggesting that these values matter, and could be leveraged to secure the future of iconic ecosystems such as the GBR.